Healthcare professionals' perceptions of fatigue experienced by people with IBD. (1st August 2014) - Czuber-Dochan, Wladyslawa; Norton, Christine; Bredin, Francesca; Darvell, Marcia; Nathan, Indira; Terry, Helen
Abstract: Background and aims: Fatigue is one of the top complaints of people with inflammatory bowel disease (IBD); however this is often not addressed in clinical consultations. This study aimed to gain an understanding of healthcare practitioners' (HCPs) perception of IBD fatigue as experienced by people with IBD. Methods: Descriptive phenomenology was conducted with 20 HCPs who work with people with IBD. In-depth semi-structured interviews were audio recorded and transcribed verbatim. Colazzi's framework was used to analyse data. Results: Three themes and several sub-themes were identified. The main themes were: the phenomenon of fatigue as perceived by HCPs; the impact of fatigue on patients' lives; and the methods used by HCPs to deal with fatigue. Fatigue was identified as an important, but difficult and frustrating, symptom to understand. HCPs reported that fatigue impacts on the emotional, private and public aspects of patients' functioning, however there were few methods suggested on how to assess and manage the fatigue. Many expressed frustration at not being able to help more. Conclusions: The study identified a gap in HCPs' knowledge and their understanding of the complexity of IBD fatigue and the full impact that IBD fatigue has on people's lives. There is a need for more research-generated evidence to enhance our understanding of the concept and the factors associated with IBD fatigue. Advances in the assessment and management of this complicated and poorly understood clinical symptom are needed in order to help enable HCPs to provide better quality care to people affected by IBD and IBD fatigue.